M. Contu (ed.), L’emigrazione sarda in Argentina e Uruguay (1920-1960). I casi di Guspini, Pabillonis, Sardara e Serrenti (Altre Modernità, 2009)
M. Contu (ed.), L’emigrazione sarda in Argentina e Uruguay (1920-1960). I casi di Guspini, Pabillonis, Sardara e Serrenti